2020
DOI: 10.1155/2020/8592869
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Triple‐Blind, Placebo‐Controlled, Add‐On Clinical Trial to Evaluate the Efficacy of Emblica officinalis in Uncontrolled Hypertension

Abstract: Introduction. Emblica officinalis (EO) has some cardiovascular effects, and there are some animal studies that show its antihypertensive effect. This study was conducted to determine the effect of combination of EO with standard therapy on the systolic blood pressure (SBP) and diastolic blood pressure (DBP) in patients with uncontrolled hypertension. Materials and Methods. This was a randomized, triple-blind, placebo-controlled, 8-week study. Ninety-two patients with uncontrolled hypertension despite taking hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Likewise, diastolic blood pressure showed a notable decrease of 12.3% ± 7.87% in the P. emblica group, in contrast to a 3.88% ± 7.98% decrease in the placebo group. Importantly, throughout the study duration, no toxic side effects were observed in any of the patients, underscoring the safety profile of P. emblica in this context (Ghaffari et al, 2020). For a visual representation of the mechanism, please refer to Figure 7.…”
Section: Antihypertensive Activitymentioning
confidence: 55%
See 1 more Smart Citation
“…Likewise, diastolic blood pressure showed a notable decrease of 12.3% ± 7.87% in the P. emblica group, in contrast to a 3.88% ± 7.98% decrease in the placebo group. Importantly, throughout the study duration, no toxic side effects were observed in any of the patients, underscoring the safety profile of P. emblica in this context (Ghaffari et al, 2020). For a visual representation of the mechanism, please refer to Figure 7.…”
Section: Antihypertensive Activitymentioning
confidence: 55%
“…In a rigorously conducted study by Ghaffari et al (2020), a randomized, triple-blind, and placebo-controlled research approach was employed to investigate the antihypertensive effects of P. emblica. The study included 92 patients who were randomly Frontiers in Pharmacology frontiersin.org 14 assigned to two groups.…”
Section: Antihypertensive Activitymentioning
confidence: 99%
“…In the current study, the ACE inhibitory activity of the amla powder and kokum (powder and slice) extracts was found to be high even at one-fifth dilutions of the extracts, thereby indicating their potent antihypertensive activity. In a clinical study, an eight-week combination therapy of amla with antihypertensive drugs was found to significantly reduce the systolic blood pressure and diastolic blood pressure in patients with hypertension when compared to control (placebo) group [ 66 ]. In the current study, the in vitro ACE inhibition results indicates that amla and kokum, in addition to the other selected botanicals, can be incorporated in dietary support strategies as slices or powder to counter chronic hypertension commonly associated with type 2 diabetes and other NCDs.…”
Section: Resultsmentioning
confidence: 99%
“…Berbagai teknik yoga mulai dari relaksasi, pernafasan, hingga praktek terintegrasi telah diteliti mampu mengatasi hipertensi (Tyagi & Cohen, 2014). Setiap bahan-bahan pada ramuan Rasahara secara tunggal telah dibuktikan efek antihipertensinya baik pada percobaan ke manusia ataupun hewan (Ghaffari et al, 2020;Prasad et al, 2017;Sahoo et al, 2015).…”
Section: Pembahasanunclassified